An Analysis of the Driving Factors of the Desertification in the Desert-Oasis Transition Zone Utilizing the Perspective of the Marx's Concept of Nature: A Case Study of the Ulan Buh Desert. (27th June 2022) - Xie, Yuan; Zhao, Xiaodi; Zhou, Huoyan
Abstract : The Ulan Buh Desert is in an arid and semiarid area in China, which features an exceedingly vulnerable ecological environment and has severe desertification. Based on Marx's explanations for the human-nature relationship, this research applies the remote sensing data and meteorological and socioeconomic data from 2006 to 2018 to conduct a quantitative analysis of the desertification driving factors in the Ulan Buh Desert by adopting the method called multivariate random forest regressor. The findings of the research suggested that the average model employing a random forest algorithm is found to be 84.20%. The desertification in the Ulan Buh Desert showed a declining trend from 2006 to 2018, and the reversed desertification areas mainly are expanded into the hinterlands of the Ulan Buh Desert and along the Yellow River. While the main driving factor of desertification was found to be related to human activities, which were undertaken based on natural factors, the regional desertification was mainly attributed to human economic activities, population density, and altitude. Thus, lessening the excessive impact of human activities on the desert ecosystem would be crucial to protecting the local desert resources and increasing the ecological capacity of the desert ecological capacity. As a consequence, to reduce pressure on land, expand environment capacity, protect vegetation cover in the region, and lower the probability of triggering desertification, the interaction between human beings and nature should be carefully managed and observed.